Consumers’ Perception of the Benefits and Challenges of Organic Food Consumption and Supply - Komathy Sandran; Nor Farah Syahirah Ibrahim; Siti Zulaikha Ahmad Fadzil; Ooi Kar Wern; Norlaile Salleh Hudin; Noraine Salleh Hudin; Risyawati Mohamed Ismail (International Journal of Supply Chain Management, 2020)
Despite growing concern on the quality and safety of food available in the market, only a small portion of consumers purchase organic food products. Therefore, this study aims to explore the perception of consumers towards the benefits and challenges of organic food consumption. For that purpose, a semi-structured interview was conducted with three organic food consumers in Tanjung Malim, Perak and data were analysed by using thematic analysis. The findings confirmed “healthiness” and “green environment” as the benefits of organic consumption, while “high price” and “the lack of organic food availability” were described as the challenges in organic food consumption. The implication of the study is that campaigns towards organic food consumption should be focusing on the healthier eating and environmental-friendliness of organic food production. Moreover, organic food producers need to focus on reducing the cost of organic food production to reduce price and increase distribution of organic food to penetrate more market segments.